Effect of Visual Attention on Binocular Fusion Limits. (October 2018) - Kihara, Ken; Ono, Hiroshi
We examined the effect of visual attention on binocular fusion limits by using Posner's spatial cueing paradigm that entails cued shifts of attentional focus. Results showed that attention decreases the fusion limit. Observers perceived diplopia of a binocular line within +/−26.5 arcmin disparity (+/− correspond to uncrossed and crossed, respectively) more frequently when it was oriented to the line than when cued attention was directed elsewhere. We discuss the results in terms of attention increasing spatial resolution and contrast sensitivity.